Characteristics of Circulating Donor Human Leukocyte Antigen-specific Immunoglobulin G Antibodies Predictive of Acute Antibody-mediated Rejection and Kidney Allograft Failure. Issue 6 (June 2015) - Kannabhiran, Dinesh; Lee, John; Schwartz, Joseph E.; Friedlander, Rex; Aull, Meredith; Muthukumar, Thangamani; Campbell, Sean; Epstein, David; Seshan, Surya V.; Kapur, Sandip; Sharma, Vijay K.; Suthanthiran, Manikkam; et al.
Abstract : Background: Characteristics of pretransplant antibodies directed at donor human leukocyte antigen (HLA) donor-specific antibodies (DSA) associated with adverse outcomes in kidney transplant recipients are being elucidated but uncertainties exist. Methods: We prospectively screened pretransplant sera from 543 kidney recipients using single antigen bead assays and identified 154 patients with and 389 without DSA. We investigated the association of DSA features to acute rejection and graft failure. Results: One-year acute rejection incidence was higher in DSA-positive group ( P < 0.001), primarily due to antibody-mediated rejection (AMR, 13% vs. 1.8%, P < 0.001) and not T cell–mediated rejection (ACR, 5% vs.6%, P = 0.65). The sum of mean fluorescence intensity of DSA (DSA MFI-Sum) of 6, 000 or higher (OR, 18; 95% CI, 7.0–47; P < 0.001) and the presence of DSA against both HLA class I and II (OR, 39; 95% CI, 14–106; P < 0.0001) predicted 1-year AMR, independent of other covariates. Calculated panel reactive antibody and a positive flow cytometry cross-match result were associated with AMR by bivariate analysis but neither was an independent predictor in a multivariable regression analysis that included DSA-MFI-Sum or HLA DSA class. In multivariable Cox proportional hazards models, the covariate-adjusted hazard ratio for graft failure was 2.03 (95%CI, 1.05–3.92; P = 0.04) for DSA MFI-Sum of 6, 000 or higher and 2.23 (95% CI, 1.04–4.80; P = 0.04) for class I and II DSA. Prediction of graft failure was not independent of AMR. Conclusion: Our study suggests that DSA MFI-Sum and HLA class of DSA are characteristics predictive of AMR and graft failure. The elevated risk of graft failure in those with the identified features of DSA is attributable to increased risk of AMR. Abstract : The study investigates the association of donor-specific antibodies (DSA) with renal allograft outcomes. Higher titred DSA and DSA against both class I and II HLA are independently associated with a higher incidence of antibody-mediated rejection in the first year after transplant. Supplemental digital content is available in the text.